2005
DOI: 10.1097/01.ju.0000152292.97692.e1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Augmentation Cystoplasty Is Associated With Earlier Rather Than Increased Artificial Urinary Sphincter Infection

Abstract: Our results suggest that, while simultaneous augmentation cystoplasty and artificial urinary sphincter implantation lead to an initial increase in prosthesis infection, this difference disappears after 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In our study, two patients underwent concomitant augmentation cystoplasty without any complications, and delayed augmentation cystoplasty was not associated with a higher risk of reoperation. This corroborates the data from Catto et al, 26 who reported no difference in the long‐term efficacy of staged or simultaneous cystoplasty and AUS implantation. Two patients were successfully treated with botulinum toxin injection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, two patients underwent concomitant augmentation cystoplasty without any complications, and delayed augmentation cystoplasty was not associated with a higher risk of reoperation. This corroborates the data from Catto et al, 26 who reported no difference in the long‐term efficacy of staged or simultaneous cystoplasty and AUS implantation. Two patients were successfully treated with botulinum toxin injection.…”
Section: Discussionsupporting
confidence: 91%
“…24 Whether to perform concomitant or delayed augmentation cystoplasty to prevent renal deterioration in this population is still debated. 20,26 In our study, two patients underwent concomitant augmentation cystoplasty without any complications, and delayed augmentation cystoplasty was not associated with a higher risk of reoperation. This corroborates the data from Catto et al, 26 who reported no difference in the long-term efficacy of staged or simultaneous cystoplasty and AUS implantation.…”
Section: T a B L E 3 Risk Factors For Explantationmentioning
confidence: 53%
See 1 more Smart Citation
“…Several surgical options are available to treat co‐existing stress urinary incontinence (SUI), however, AUS is the outlet procedure that offers the maximum chance of spontaneous voiding. AUS insertion can be performed concomitantly with AC without any increased morbidity, infection rate or change to success rates of either procedure [137,138]. There is a theoretical concern that urethral trauma due to CISC in patients with both an AC and an AUS may introduce bacteria into the urine and risk infective complications.…”
Section: Long‐term Complications (Table 1) [131520222387–94]mentioning
confidence: 99%